Corrosion of conductor rolls in the electrogalvanizing line at Ternium Siderar - Egli, Walter Alfredo (2013)
Conductor rolls in the electrogalvanizing line are made of Duplex Stainless Steel (DSS) and after some time in service they suffer surface deterioration leading to surface defects and rejections in high quality products. Repassivation kinetics and susceptibility to pitting corrosion for the austenitic and ferritic phases were studied. An electrochemical treatment that reproduces the actual industrial corrosive situation was applied to test different alloys in the laboratory. The Hastelloy C22 showed the best performance and was evaluated in the line during a complete production batch. The new roll presented a slight deterioration, much lower than the DSS rolls.